Stretta Radiofrequency Treatment for GERD: A Safe and Effective Modality - Mark Franciosa; George Triadafilopoulos; Hiroshi Mashimo (Gastroenterology Research and Practice)
Gastroesophageal reflux disease is one of the leading gastrointestinal disorders. Current treatments include lifestyle modifications, pharmacological therapies, surgical fundoplications, and, more recently, endoscopic procedures. The rising concern of long-term side effects of the popular proton-pump inhibitors and the more recent evidence raising doubts about the durability of fundoplication have spurred reinterest in endoscopic procedures to treat reflux disorders. In the aftermath of several innovative antireflux procedures that were introduced and failed clinically or financially over the past decade, there is lingering confusion regarding the merits of the presently available interventions. This paper focuses on one endoscopic procedure, Stretta, which now enjoys the longest experience, a recent meta-analysis, and robust data supporting its safety, efficacy, and durability. Stretta reduces esophageal acid exposure, decreases the frequency of transient lower esophageal relaxation, increases patient satisfaction, decreases medication use, and improves quality of life. As such, this procedure remains a valuable nonsurgical treatment option in the management of gastroesophageal reflux disease.